Embracing Diversity: The Role of Islamic Tolerance in Indonesia's Multicultural Society - Ishak, Dede; Albustomi, Ahmad Gibson (UIN Sunan Gunung Djati Bandung, 2025)
Indonesia is a multicultural society religious, ethnic and cultural, so it is necessary to have mutual respect and respect to respond to these differences. Islam is a religion that the Indonesian people widely embrace, so it is necessary to have a tolerant attitude in responding to a multicultural society. Therefore, from this problem, the author is interested in studying the concept of tolerance from an Islamic perspective. The method used in this writing is the study of literature by examining more deeply both from books, articles and other media related to the theme of writing. From the results of this discussion, it can be concluded that tolerance is a commendable attitude that must be possessed by every human being in daily life, where fellow human beings respect each other within the boundaries outlined by Islam. The teachings of Islam always command its people to maintain good relations with others, including other believers. Islam was born with universal and tolerant teaching values.